Field Performance Evaluation of a Mechatronic Reflector System in a Private mmWave Network Environment - Simon Hager; Marcel Kaudewitz; Florian Schmickmann; Stefan Bocker; Christian Wietfeld (IEEE Open Journal of the Communications Society, 2025)
6G millimeter-wave (mmWave) networks are expected to provide widespread multi-Gbit/s connectivity. However, increased sensitivity to obstacle blockage leads to underconnected shadow regions, motivating the introduction of intelligent reflecting surfaces (IRSs) for efficient smart radio environments that are dynamically illuminated by anomalous reflections. Against this background, this article first presents a comprehensive analysis of the current state of IRS implementations and experimentation. We observe a scarcity of large-scale reconfigurable mmWave IRSs and insufficient experimental insights using communications equipment outside laboratory conditions. To address this gap, we develop R-HELIOS, a mechatronically reconfigurable IRS based on our geometry-based passive HELIOS IRS, which has previously been validated as a large static IRS in field studies with mmWave modems. It is complemented by a remote-control operation center that systematically orchestrates reflection behavior. The IRS research platform is then integrated into a private mmWave network environment utilizing commercial user equipments (UEs) for 6G-relevant experimentation. In an indoor factory-like scenario, we investigate an IRS beam search mechanism to improve connectivity for shadowed UEs in safety cages for machinery. Serving both UEs with a multi-armed reflection configuration maximizes the cell throughput to 2.1 Gbit/s, constituting an increase by 173 %. In a larger-scale indoor-to-outdoor setup covering an approximately 30 m2 shadowed study area, the IRS facilitates a mean downlink throughput improvement of 0.9 Gbit/s. Our study thus underscores the high potential of mmWave IRSs for static UEs. Additional measurements with a mobile user highlight the necessity for fine-grained angular beam tracking to mitigate fades at intermediate positions.